Differences in constitutive gene expression of cytochrome P450 enzymes and ATP-binding cassette transporter gene expression between a susceptible and a highly macrocyclic lactone-resistant Haemonchus contortus isolate in the absence of drug-inducible expression - Natalie Jakobs; Sandro Andreotti; Sabrina Ramünke; Georg von Samson-Himmelstjerna; Jürgen Krücken (Parasites & Vectors)
Abstract Background Anthelmintic resistance in ruminants is a widespread problem that has a severe impact on productivity and animal welfare. The helminth Haemonchus contortus is generally considered the most important parasite in small ruminants due to its high pathogenicity and the widespread occurrence of anthelmintic resistance in it. Although the molecular mechanisms associated with resistance against the anthelmintics benzimidazoles (BZs) and levamisole are relatively well understood, the resistance mechanisms against the widely used anthelmintic macrocyclic lactones (MLs) ivermectin (IVM) and moxidectin (MOX) remain poorly understood. Detoxifying enzymes and xenobiotic transporters have been frequently proposed to play a role in ML resistance in multiple organisms, including nematodes. Methods The reference genome of H. contortus was screened for cytochrome P450 genes (cyp genes) by using the Basic Local Alignment Search Tool, and maximum-likelihood phylogenetic analysis was used to assign the sequences to gene families. Fourth-stage larvae of the susceptible (McMaster) and the ML-resistant (Berlin-selected) H. contortus isolates were generated in vitro and compared regarding basal expression levels of cyp genes and ATP-binding cassette (ABC) transporters by using RNA sequencing. The resistant isolate was further incubated with 100 nM IVM or MOX for 3, 6 and 12 h, and the effects of incubation time and drugs were evaluated. Results Twenty-five cyp genes were identified in the H. contortus genome and assigned to 13 different families. The ML-resistant isolate showed significantly higher and lower constitutive expression of 13 and four cyp genes, respectively. Out of the 50 ABC transporter genes, only six showed significantly higher expression in the ML-resistant isolate, while 12 showed lower expression. The fold changes were in general low (range 0.44–5.16). Only pgp-13 showed significant downregulation in response to IVM (0.77 fold change at 6 h, 0.96 fold change at 12 h) and MOX (0.84 fold change at 12 h). In contrast, mrp-5 was significantly, albeit minimally, upregulated in the presence of IVM, but not MOX, after 12 h (1.02 fold change). Conclusions Despite little observable ML-inducible gene expression in the isolate examined here, some of the changes in the baseline expression levels might well contribute to ML resistance in the context of additional changes in a multigenic resistance model. However, neither cyp genes nor the ABC transporters appear to be the main drivers that can explain the high levels of resistance observed in the resistant isolate examined here. Graphical Abstract